Determination of internal controls for quantitative gene expression of Spodoptera litura under microbial pesticide stress - Shuang Wu; Yunmi Luo; Zhihong Zeng; Ying Yu; Shicai Zhang; Yan Hu; Lei Chen (Scientific Reports, 2024)
Abstract Quantitative real-time polymerase chain reaction (qRT-PCR) has become a commonly used method for the quantification of gene expression. However, accurate qRT-PCR analysis requires a valid internal reference for data normalization. To determine the valid reference characterized with low expression variability among Spodoptera litura samples after microbial pesticide treatments, nine housekeeping genes, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), arginine kinase, ubiquitin C, actin-5C (ACT5C), actin, ribosomal protein S13 (RPS13), tubulin, acidic ribosomal protein P0 (RPLP0) and ubiquinol-cytochrome c reductase, were evaluated for their suitability using geNorm, Normfinder, BestKeeper, RefFinder and the comparative delta CT methods in this study. S. litura larvae after direct treatment (larvae were immersed in biopesticides), indirect treatment (larvae were fed with biopesticide immersed artificial diets) and comprehensive treatment (larvae were treated with the first two treatments in sequence), respectively with Metarhizium anisopliae, Empedobacter brevis and Bacillus thuringiensis, were investigated. The results indicated that the best sets of internal references were as follows: RPLP0 and ACT5C for direct treatment conditions; RPLP0 and RPS13 for indirect treatment conditions; RPS13 and GAPDH for comprehensive treatment conditions; RPS13 and RPLP0 for all the samples. These results provide valuable bases for further genetic researches in S. litura.